Trends in Audit and Good Corporate Governance Research: A Bibliometric Analysis from 1994 to 2022 Based on Scopus Data - Rachmat Agus Santoso (Manunggal Halim Jaya, 2022)
In an increasingly complex era of globalization, the role of audit in supporting Good Corporate Governance (GCG) has become a central focus in the accounting and finance literature. The background of this research is based on the need to comprehensively understand the dynamics and developments in research related to audit and GCG, with the aim of identifying key themes, influential authors, and gaps in the existing literature. This study utilizes data from Scopus, covering 109 documents published between 1994 and 2022. Using a bibliometric approach, the study analyzes publication trends, citation rates, international collaborations, and the main themes emerging in the study of audit and GCG. The results indicate that themes such as corporate governance, earnings management, audit quality, and financial performance dominate the literature, with major contributions coming from countries like Indonesia, China, and the United Kingdom. Additionally, the study finds a decline in the relevance of certain themes, such as firm performance, highlighting the need for further research. The novelty of this research lies in identifying gaps and new research opportunities in underexplored niche themes, as well as revealing patterns of international collaboration that could enrich the literature in the future.